2009
DOI: 10.1590/s0100-06832009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Aggregate stability as affected by short and long-term tillage systems and nutrient sources of a hapludox in southern Brazil

Abstract: SUMMARYThe ability of a soil to keep its structure under the erosive action of water is usually high in natural conditions and decreases under frequent and intensive cultivation. The effect of five tillage systems (NT = no-till; CP = chisel plowing and one secondary disking; CT = primary and two secondary distings; CTb = CT with crop residue burning; and CTr = CT with removal of crop residues from the field), combined with five nutrient sources (C = control, no nutrient application; MF = mineral fertilizers ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
4
7
0
4
Order By: Relevance
“…Therefore, increasing soil organic C often leads to better soil aggregation. Similar results were reported by other authors for the tropical regions (Six et al, 1999;Madari et al, 2005;Salton et al, 2008;Veiga et al, 2009;Souza et al, 2009;Garcia and Rosolem, 2010). In addition, Six et al (1999) showed that due to the increase in organic matter, smaller aggregates coalesce into larger aggregates, improving soil structure.…”
Section: Total Organic Carbon In Fractions Of Aggregatessupporting
confidence: 90%
“…Therefore, increasing soil organic C often leads to better soil aggregation. Similar results were reported by other authors for the tropical regions (Six et al, 1999;Madari et al, 2005;Salton et al, 2008;Veiga et al, 2009;Souza et al, 2009;Garcia and Rosolem, 2010). In addition, Six et al (1999) showed that due to the increase in organic matter, smaller aggregates coalesce into larger aggregates, improving soil structure.…”
Section: Total Organic Carbon In Fractions Of Aggregatessupporting
confidence: 90%
“…In the upper 0.00-0.05 and 0.05-0.20 m layers, the NT system improved the formation level of the >2 mm aggregate but reduced the formation level of <0.053 mm aggregates, compared to the MP system, suggesting that mechanical operation reduced large-macroaggregate formation and disrupted soil macroaggregates into individual particles. Similar results have also been reported by Wohlenberg et al (2004), Veiga et al (2009 and Jiang et al (2011). The higher proportion of >2 mm aggregates and lower proportion of <0.053 mm aggregates under NT systems might be the result of the higher soil hydrophobicity, low intensity of wetting and drying cycles, higher soil C concentration or the physical and chemical characteristics of large macroaggregates making them more resistant to breaking up (Balesdent et al, 2000;Eynard et al, 2006;Vogelmann et al, 2013).…”
Section: Changes In Aggregation Distribution In Soil Profilesupporting
confidence: 84%
“…Positive effects of straw application on macroaggregate formation and stability have also been reported by other workers (Singh et al, 2007;Veiga et al, 2009;Bandyopadhyay et al, 2010).…”
Section: Changes In Aggregation Distribution In Soil Profilesupporting
confidence: 80%
“…Isso indica que a presença dos animais pode contribuir para a estabilização de agregados pelo efeito do pisoteio, ao promover a aproximação de partículas minerais. Assim, o aumento da densidade do solo pode proporcionar agregados mais estáveis (Veiga et al, 2009).…”
Section: Resultsunclassified